The Influence Of Animation Film Viewing Intensity On The Speaking Ability Of Children Aged 4–5 Years - Asih Budi Kurniawati; Salsabila Jannati 'Uyyun; Susanthi Pradini (Universitas Muhammadiyah Surakarta, 2026)
This study aims to determine the effect of the intensity of watching animated films on the speaking ability of children aged 4-5 years. The researcher used a quantitative research type with an ex-post facto method. Sampling in this study used cluster random sampling with a sample size of 75 parents as respondents. Data collection in this study used a questionnaire method with an instrument in the form of statements that parents need to fill in to obtain data on the intensity of watching animated films and children's speaking ability. The data obtained were then analyzed using a simple linear regression test processed with the help of SPSS. The results of this study explain that the intensity of watching animated films has a positive effect on children's speaking ability as evidenced in the hypothesis test with a significance value of 0.000 <0.05. High frequency of watching will affect children’s speaking skills in terms of improving sentence structure, with a percentage of 25.6%. There needs to be selection as a form of adult supervision so that animated films can stimulate children’s speaking abilities.